Crystal structure of the co-crystal O-isopropyl phenylcarbamothioate – 4,4′-bipyridine (2/1), C15H17N2OS - Yeo Chien Ing; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C15H17N2OS, triclinic, P1̄ (no. 2), a = 5.8595(3) Å, b = 9.2967(4) Å, c = 14.0545(8) Å, α = 83.320(4), β = 89.240(4), γ = 74.524(4), V = 732.71(7) Å3, Z = 2, Rgt(F) = 0.0458, wRref(F2) = 0.1231, T = 100 K.